Analysis The Effect of Entrepreneurship Education on E-Commerce Entrepreneur Motivation in Information Systems Students: Analisis Pengaruh Pendidikan Kewirausahaan terhadap Motivasi Berwirausaha E-Commerce pada Mahasiswa Sistem Informasi - Yesi Gusteti; Jujuk Juan Colin (International Journal of Management and Business (IJMB), 2020)
This research aims at analyzing the effect of entrepreneur education toward students’ entrepreneur motivation especially e-commerce on system information students of computer science faculty. Dharmas Indonesia University. Dharmasraya, West Sumatera.Curriculum of system information gives computer science approach toward business management in order to graduate students are capable to get jobs related to system information field especially in implementing of computerizing on business management. E-commerce is one of business computer-based and internet technology that have been developed rapidly and well-known recently. On line business is one of e-commerce that can be reached by many people. This research used regression linear analysis to find the effect of profit, independent, freedom, personal dream, environment and mode toward entrepreneur motivation of e-commerce on system information students at Dharmas Indonesia University(UNDHARI). Keywords: entrepreneur, motivation, e-commerce.